Synthesis and Characterization of Schiff Bases Coordination Compounds of Lanthanide(III) Perchlorates - Arora, Kishor; Sharma, Mukesh; Sharma, K.P. (Asian Journal of Chemistry, 2010)
Dicyanoethylation of m-toluidine was carried out by treating the aromatic primary amine with acryonitrile in acetic acid in presence of cuprous chloride. The cyanoethylated amine on formylation gave 2-methyl-4-NN-bis-2'-cyanoethylaminobenzaldehyde. The resulted aldehyde gave Schiff bases 2-methyl-4-NN-bis-2′-cyanoethylaminobenzylidineaniline (MCEABAB), 2-methyl-4-NN-bis-2′-cyanoethylaminobenzylidine p-chloroaniline (MCEABCAB), 2-methyl- 4-NN-bis-2′-cyanoethylaminobenzylidine p-toludine (MCEABPT) and 2-methyl-4-NN-bis-2′- cyanoethylaminobenzylidine p-fluoroaniline (MCEABFAB) with aniline and three different substituted anilines. Lanthanide oxides viz., lanthanum oxide, praseodymium oxide and neodymium oxide were chosen to synthesize new complexes, heaving a general formula [Ln(L)6(ClO4)3] [where Ln = La, Pr and Nd; L = MCEABAB, MCEABCAB, MCEABPT and MCEABFAB]. In all twelve new lanthanide(III) perchlorate complexes of Schiff bases have been prepared. Elemental analyses, molecular weight, melting point, conductivity measurement, spectral studies, thermal analysis and microbial activities of the complexes were carried out.